(untitled) (e-Journal of Linguistics, 2024)
The goal of this study is to look at how Taylor Swift uses figurative language in her song All Too Well (10 Minutes Version). The primary purpose of this study is to discover the meaning behind the figurative language used in song lyrics. A descriptive qualitative method was used to collect the data. There are various kinds of figurative language applied to express meaning in the song, but the writer only focuses on two of them, namely personification and simile. To summarize the analysis, the song’s figurative language, which draws on personification and simile, creates an effective tool for portraying the story’s deep and sensitive emotions, such as sense of loss, emptiness, and sadness.